2004
DOI: 10.1387/ijdb.15005569
|View full text |Cite
|
Sign up to set email alerts
|

Patterning a multi-headed mutant in Hydractinia: enhancement of head formation and its phenotypic normalization.

Abstract: In a mutant strain of Hydractinia (Cnidaria: Hydrozoa), the polyps develop ectopic supernumerary tentacles and heads (hypostomes) after an initial phase of wild-type growth. In order to elucidate the molecular mechanisms implicated in the development of aberrant phenotypes, we tried to enhance or suppress the expressivity of this hypomorphic mutation by exposing subclones to factors supposedly influencing pattern formation. Upon iterated treatment with alsterpaullone, an inhibitor of GSK-3, the formation of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
3
13
0
Order By: Relevance
“…GSK-3β is a downstream element in the cascade, but its blockage led to the establishment of upstream Wnt-expressing centers. This positive feedback loop corresponds aslo well to previous studies (Holstein et al, 2003;Müller et al, 2004b). Here we show that blockage of GSK-3β increases budding activity in terms of a novel experimental phenotype: not only more buds per stolon or per colony area are produced, but the size of the bud fields is tremendously enlarged.…”
Section: Discussionsupporting
confidence: 91%
“…GSK-3β is a downstream element in the cascade, but its blockage led to the establishment of upstream Wnt-expressing centers. This positive feedback loop corresponds aslo well to previous studies (Holstein et al, 2003;Müller et al, 2004b). Here we show that blockage of GSK-3β increases budding activity in terms of a novel experimental phenotype: not only more buds per stolon or per colony area are produced, but the size of the bud fields is tremendously enlarged.…”
Section: Discussionsupporting
confidence: 91%
“…3 D-1) depends on both tips sharing the same histocompatibility alleles. If applied to the growing medium at supra-natural concentration, SIF causes complete transformation of polyps into stolons (Lange and Müller, 1991;Müller et al, 2004b).…”
Section: Compartments Of the Colony Spacing Patterns And Division Ofmentioning
confidence: 99%
“…Like in Hydra, blocking GSK3 generally leads to oralization. Polyps of Hydractinia treated with paullones (Müller et al, 2004b) transform to phenocopies of a multi-headed mutant (Fig. 2D) (Müller, 2002).…”
Section: Activation Of the Wnt Pathway Leads To Oralization In Hydracmentioning
confidence: 99%
“…In cnidarians, components of the canonical Wnt signaling pathway are thought to be involved in the establishment of the anteriorposterior (AP) axis (Amiel and Houliston, 2009;Broun et al, 2005;Hobmayer et al, 2000;Kusserow et al, 2005;Lee et al, 2007;Müller et al, 2004b;Plickert et al, 2006). The above studies, and others, have shown that several Wnt genes are expressed asymmetrically in the adult form, the polyp, with the highest expression levels around the mouth area (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear -catenin was reported in the corresponding pole of the Nematostella embryo (Wikramanayake et al, 2003). Finally, it has been shown that misexpression of Wnt3, frizzled (Momose et al, 2008;Momose and Houliston, 2007) and -catenin (Gee et al, 2010), as well as blocking of GSK3 (Hassel et al, 1993;Müller et al, 2004b), affects AP axis formation, suggesting that a Wnt-mediated organizer acts to specify the position of the cnidarian head (Broun et al, 2005). There is no functional data in the literature on the effect of Wnt pathway inhibition on aboral structures (Tanaka and Weidinger, 2008).…”
Section: Introductionmentioning
confidence: 99%